From Conversation to Contract: The Notary's Role in Nineteenth-Century Montreal - Olson, Sherry; Poutanen, Mary Anne (Urban History Review / Revue d'histoire urbaine, 2024)
Keywords: Famille; Notaires

« Il s'en tuë jusques dans les jardins de Québec ». La place des animaux sauvages dans la ville (Québec et Montréal, 1663-1763) - Riguelle, William (Urban History Review / Revue d'histoire urbaine, 2024)
Keywords: Alimentation; Faune

Recovering Identities from the Judicial Archives of Quebec - Olson, Sherry; Poutanen, Mary Anne (Histoire sociale / Social History, 2024)
Keywords: Archives; Enfants; Famille; Femmes

Intimacies in the Neighbourhood: Revisiting Sex Commerce, Families, and Criminal Court Records in Early Nineteenth-Century Montreal - Poutanen, Mary Anne (Family and Justice in the Archives. Historical Perspectives on Intimacy and the Law, 2024)
Keywords: Criminalité; Famille; Femmes; Prostitution

Inventories, Interiors, and Women’s Ambitions: Strategies of Property Ownership in Three Mid-19th Century Montreal Public Houses - Poutanen, Mary Anne (Urban History Review/Revue d'histoire urbaine, 2023)
Keywords: Femmes

L’ancien cimetière Saint-Antoine (1799-1854) et son voisin rural à Pointe-aux-Trembles (1709-1843) : analyse comparative de la mortalité des enfants de deux populations du XIXe siècle sur l’île de Montréal - Duchemin, Emmanuelle (Université de Montréal, 2023)
Keywords: Enfants; Mortalité; Pointe-aux-Trembles; Saint-Antoine

Liens d’amitié, de parenté et d’appartenance à une collectivité : genre, itinérance et aide mutuelle à Montréal au début du XIXe siècle - Poutanen, Mary Anne (Écrire la ville. Pouvoirs, urbanités et modernités dans l’espace québécois (XIXe-XXe siècles), 2023)
Keywords: Femmes; Itinérance

Les quartiers de la grande bourgeoisie: le cas du Golden Square Mile à Montréal - Bérubé, Harold (Histoire des villes nord-américaines, 2022)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (Études d'histoire du Québec / Studies on the History of Quebec, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."--
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

« Se soumettre de bon coeur à son mari »: le combat d'une femme face à l'autoritarisme marital - Lamonde, Yvan (Presses de l'Université Laval, 2022)
Keywords: Avocats; Doutre, Joseph; Femmes; Guibord, Joseph; Institut canadien; Mariage; Renaud, Marie-Zoé-Aimée; Trudel, François-Xavier-Anselme; Ultramontains

Left Out of the Official History. The Women of St Anne's Market - Poutanen, Mary Anne; Olson, Sherry (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Femmes; Marchés; Sainte-Anne (marché); Travail

Everyday Life at St Anne's Market. Very, Very Unsanitary! - Roy, Christian (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Archéologie; Marchés; Sainte-Anne (marché); Égouts

Railways and the Urban Soundscape: Montreal, 1850s-1950s - Rudy, Jarrett; Fahrni, Magda; Kenny, Nicolas (Urban History Review / Revue d'histoire urbaine, 2022)
Keywords: Chemins de fer; Paysages

Going Together Like a Horse and Carriage: Rentier Marriages and Property Accumulation in Montréal, 1825-1903 - Sweeney, Robert C. H. (Histoire sociale / Social History, 2021)
Keywords: Famille; Logement; Mariage

The Goode House (The Westmount Historian, 2021)
Keywords: Conservation; Famille; Jardins; Patrimoine

Un territoire à habiter et à aménager (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2021)
Keywords: Ahuntsic; Cartierville; Logement; Quartiers; Sault-au-Récollet

Quand le temps s'arrête: une promenade dans le jardin de la maison Goode / Window to the Past: A Walk in the Garden of the Goode House - Adib, Danièle; Crépeau, Antoine (The Westmount Historian, 2021)
Keywords: Jardins

Three Generations of Goode Family - Breslaw, Caroline (The Westmount Historian, 2021)
Keywords: Famille

Note de recherche. Les journaliers dans le district de Montréal en 1831 - Dessureault, Christian (Revue d'histoire de l'Amérique française, 2021)
Keywords: Famille; Recensements; Travail

Les Irlandais catholiques de Montréal : genèse d'une communauté, 1800-1834 - Duchesne, Jonathan (Université du Québec à Montréal, 2021)
Keywords: Famille; Irlandais; Mariage

La tutelle des enfants mineurs au Bas-Canada: autorité domestique, traditions juridiques et masculinités - Garneau, Jean-Philippe (Revue d'histoire de l'Amérique française, 2021)
Keywords: Enfants; Famille; Femmes; Mariage; Veuvage

Une famille pionnière de la rue Dandurand: celle de George Ineson - Guilbault, Normand; Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2021)
Keywords: Famille; Logement; Quartiers; Rosemont

Une histoire sociale de la prostitution: Montréal, 1800-1850 - Poutanen, Mary Anne (Les éditions du remue-ménage, 2021)
Keywords: Femmes; Prostitution

Oubliées de l'histoire officielle. Les femmes du marché Sainte-Anne - Poutanen, Mary Anne; Olson, Sherry (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Femmes; Marchés; Sainte-Anne (marché); Travail

Le marché Sainte-Anne au quotidien. Plus insalubre qu'il n'y paraît! - Roy, Christian (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Archéologie; Marchés; Sainte-Anne (marché); Égouts

British Philanthropists and the Imperial Imagination or The Case of the Canadians Distressed by Fire at Montreal - Eamon, Michael (Canadian Historical Review, 2020)
Keywords: Britanniques; Incendies; Philanthropie

Le Plateau agricole (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2020)
Keywords: Alimentation; Baron (côte à); Côtes; Institut des sourdes-muettes; Jardins; Meunerie; Plateau Mont-Royal

Women in Westmount (The Westmount Historian, 2020)
Keywords: Femmes; Peinture; Élections

L’intimité française avec la " sauvagerie " à Montréal aux 17e-18e siècles - Deslandres, Dominique (Dix-huitième siècle, 2020)
Keywords: Autochtones; Criminalité; Délinquance; Français

Cohabitation, exploitation et nuisances à Montréal et à La Nouvelle-Orléans : les relations entre les populations urbaines et animales, 1840-1890 - Gagnon, Benjamin (Université du Québec à Trois-Rivières, 2020)
Keywords: Alimentation; Faune

Trouble at the Edge of Town: Policing Montreal’s Urban Periphery in the Middle of the Nineteenth Century - Horner, Dan (Micro-Geographies of the Western City, c.1750-1900, 2020)
Keywords: Irlandais; Lachine (canal); Police

Eau courante, toilettes à eau et dernières latrines à Montréal, 1856-1915 - Lauzon, Gilles (Revue d'histoire de l'Amérique française, 2020)
Keywords: Aqueduc; Égouts

"Every Attention Will Be Paid to the Satisfaction of the Guests": Angélique Archambault and Donegana’s Hotel, 1852-1864 - Poutanen, Mary Anne (Sharing Spaces: Essays in Honour of Sherry Olson, 2020)
Keywords: Femmes; Hôtellerie; Mariage

The Perils of Sex Work in Montreal: Seeking Security and Justice in the Face of Violence, 1810–1842 - Poutanen, Mary Anne (The Violence of Work: New Essays in Canadian and US Labour History, 2020)
Keywords: Prostitution

Public Houses and Hidden Networks: Roles of Women in Mid-Nineteenth-Century Montreal - Poutanen, Mary Anne; Olson, Sherry (Micro-Geographies of the Western City, c.1750-1900, 2020)
Keywords: Auberges; Famille; Femmes; Hôtellerie

Histoire des communautés noires au Québec et à Montréal (1ère partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
Keywords: Esclaves; Noirs

Histoire des communautés noires au Québec et à Montréal (2e partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
Keywords: Chemins de fer; Musique; Noirs; Travail

En rade: marins à Montréal (1851-1896) - Bélisle-Desmeules, David (Domaine histoire, 2019)
Keywords: Navigation; Port; Travail; Vieux-port

«Toujours je sens mon âme se balancer entre les joies et les peines»: le paysage émotionnel de Marie-Louise Globensky (1849-1919) observé à travers ses écrits personnels - Doucet, Sophie (Université du Québec à Montréal, 2019)
Keywords: Bourgeoisie; Femmes

Le travail des femmes célibataires de l'élite et la famille pendant la période préindustrielle à Montréal - Fortin, Jonathan (L'argent des familles. Pratiques et régulations sociales en Occident aux XIXe et XXe siècles, 2019)
Keywords: Famille; Femmes; Fourrure; Marchands; Travail

Familles montréalaises et élection de tutelle au temps du choléra: genre, appartenance ethnique et pratique judiciaire - Michaud-Guindon, Alexandre (Université du Québec à Montréal, 2019)
Keywords: Choléra; Droit; Famille; Mortalité; Veuvage; Épidémies

Montreal Property-Owners of the 1850s: "Born or to Be Born" - Olson, Sherry (L'argent des familles. Pratiques et régulations sociales en Occident aux XIXe et XXe siècles, 2019)
Keywords: Droit; Enfants; Famille; Logement

Déjouer la fatalité. Pauvreté, familles et institutions - Petitclerc, Martin (Écomusée du fier monde, 2019)
Keywords: Famille; Pauvreté

Reinforcing racial hierarchy through visual culture : black enslaved children in New France and early Quebec (1700-1834) - Trahan-Thomassin, Marilou (Université McGill, 2019)
Keywords: Enfants; Esclaves; Noirs; Peinture; Publicité

L’émergence d’un mouvement. Les premières sociétés de secours mutuels canadienne-française à Montréal, (1851-1867) - Bischoff, Peter C. (Cap-aux-Diamants, 2018)
Keywords: Assurance; Travail; Union Saint-Joseph

Montreal's Network of Social Regulation - Fecteau, Jean-Marie; Harvey, Janice (Montreal: The History of A North American City, 2018)
Keywords: Communautés religieuses; Femmes; Hôpitaux; Pauvreté

Population, Social Identities, and Daily Life - Gauvreau, Danielle (Montreal: The History of A North American City, 2018)
Keywords: Famille; Femmes; Irlandais; Mortalité; Travail; Veuvage

Vertiges. Journal, 1867-1868 - Papineau, Azélie (Études québécoises, 2018)
Keywords: Bourgeoisie; Enfants; Famille; Mariage; Papineau (famille)

Labour and the Montreal Working Class in the Nineteenth Century - Petitclerc, Martin (Montreal: The History of A North American City, 2018)
Keywords: Chevaliers du Travail; Conseil des métiers et du travail de Montréal; Grande Association; Grèves; Pauvreté; Syndicats internationaux; Travail

La grève générale des charpentiers-menuisiers de Montréal, 1833–1834 : réévaluation d’un acte fondateur autour du concept de légitimité - Tremblay, Robert (Labour / Le travail, 2018)
Keywords: Charpentiers; Grèves; Libéralisme; Maçons; Menuisiers

Daily Life in Montreal during the Eighteenth Century - Turcot, Laurent (Montreal: The History of A North American City, 2018)
Keywords: Auberges; Cabarets; Danse; Hôtellerie; Marchés; Rues; Théâtre; Vêtements

Sur le chemin du paradis: les joies d’aimer, de croire et de s’accomplir de Marie-Louise Globensky (1849-1919) - Doucet, Sophie (Revue d'histoire de l'Amérique française, 2017)
Keywords: Bourgeoisie

Lady Cartier, épouse humiliée, Patriote rejetée - Lachance, Micheline (Montréal en tête, 2017)
Keywords: Cartier, Georges-Étienne; Fabre (famille); Mariage; Partis politiques; Rouges; Rébellions

Les bourgeois "canadiens". Seconde tranche (1800-1860) - Lapierre, Michel (Montréal en tête, 2017)
Keywords: Bourgeoisie; Hommes d'affaires; Marchands; Masson, Joseph; Persillier-Lachapelle (famille); Rébellions

"Due Attention Has Been Paid to All Rules": Women, Tavern Licences, and Social Regulation in Montreal, 1840–1860 - Poutanen, Mary Anne (Histoire sociale / Social History, 2017)
Keywords: Femmes

Alimentation, commerce et patrimoine: documenter les acteurs du Vieux-Montréal victorien 1850-1880 - Burgess, Joanne (Laboratoire d'histoire et de patrimoine de Montréal, 2016)
Keywords: Alimentation; Commerce de détail; Magasins; Patrimoine; Quartiers; Vieux-Montréal

La Babylone des marins : Marins hauturiers à Montréal 1851-1896 - Bélisle-Desmeules, David (Université de Montréal, 2016)
Keywords: Alcool; Navigation; Port; Taverne Joe Beef

Un premier cimetière paroissial - Gagné, Gérard (Lumières sous la ville. Quand l'archéologie raconte Montréal, 2016)
Keywords: Cimetières; Notre-Dame (église); Églises

Les céramiques de la glacière Gervaise : le consumérisme chez la classe aisée montréalaise au milieu du XVIIIe siècle - Johnson Gervais, Mélanie (Université de Montréal, 2016)
Keywords: Archéologie

Les bourgeois "canadiens". Première tranche (1800-1860) - Lapierre, Michel (Montréal en tête, 2016)
Keywords: Berthelet, Antoine-Olivier; Bourgeoisie

Slavery, Geography and Empire in Nineteenth-Century Marine Landscapes of Montreal and Jamaica - Nelson, Charmaine A. (Routledge, 2016)
Keywords: Africains; Esclaves; Noirs; Paysages; Peinture

Conforme? Une histoire sociale du vêtement masculin chez les élites de Montréal, 1837-1918 - Villeneuve, Louis-Étienne (Université du Québec à Trois-Rivières, 2016)
Keywords: Bourgeoisie; Vêtements

Patates, pain, et lard salé valaient-ils mieux que céréales, bacon et boeuf haché? La diète quotidienne et la santé au Québec, 1861-1941 - Durand, Caroline (Canadian Bulletin of Medical History, 2015)
Keywords: Alimentation; Diététique; Pauvreté

Rosalie Cadron-Jetté (1794-1864) au service des filles-mères rejetées par la société - Lachance, Micheline (Montréal en tête, 2015)
Keywords: Bourget, Ignace; Cadron, Marie-Rosalie; Communautés religieuses; Soeurs de Miséricorde; Évêques

Beyond Brutal Passions. Prostitution in Early Nineteenth-Century Montreal - Poutanen, Mary Anne (Study on the History of Quebec/Études d'histoire du Québec, 2015)
Keywords: Femmes; Prostitution

Se construire et s'affirmer par les lieux. Un regard sur les présences autochtones à Montréal - Comat, Ioana (Université Laval, 2014)
Keywords: Autochtones; Centre d'amitié autochtone

De Marie de L'Incarnation à Nelly Arcan. Se dire, se faire par l’écriture intime - Smart, Patricia (Essais et Documents, 2014)
Keywords: Dessaulles, Henriette (Fadette); Famille; Femmes; Le Normand, Michelle; Marchand-Dandurand, Joséphine; Mariage; Papineau (famille); Rocbert de La Morandière, Élizabeth (Bégon, Élizabeth)

Journaux de jeunes filles: vers un moi autonome - Smart, Patricia (De Marie de L'Incarnation à Nelly Arcan. Se dire, se faire par l’écriture intime, 2014)
Keywords: Dessaulles, Henriette (Fadette); Famille; Femmes; Le Normand, Michelle; Mariage; Écrivains

On ne naît pas mère, on le devient : le parcours de Julie Papineau - Smart, Patricia (De Marie de L'Incarnation à Nelly Arcan. Se dire, se faire par l’écriture intime, 2014)
Keywords: Famille; Femmes; Mariage; Papineau (famille); Papineau, Louis-Joseph; Rébellions

Le contenu publicitaire de la presse québécoise aux XIXe et XXe siècles, une source à explorer - Couvrette, Sébastien (Médias 19, 2013)
Keywords: Minerve (La); Patrie (La); Publicité

Les couturières de Montréal au XVIIIe siècle - Gousse, Suzanne (Septentrion, 2013)
Keywords: Confection; Femmes

Journaux personnels des filles de Pierre-Joseph Oliver Chauveau (1855-1876). Deuxième partie: de la chronique à la réflexion - Mathieu, Jocelyne (Les Cahiers des Dix, 2013)
Keywords: Bourgeoisie; Chauveau, Pierre-Joseph-Olivier

Silver and Hotcakes and Beer: Irish Montreal in the 1840s - Olson, Sherry (Canadian Ethnic Studies / Études ethniques au Canada, 2013)
Keywords: Auberges; Irlandais

''To shudder at the bare recital of those acts'': Child Abuse, Family, and Montreal Courts in the Early Nineteenth Century - Pilarczyk, Ian C. (Essays in the History of Canadian Law: Quebec and the Canadas, 2013)
Keywords: Criminalité; Enfants; Famille; Tribunaux

Lacorne Saint-Luc: l'odyssée d'un noble, 1711-1784 - Saint-Pierre, Marjolaine (Septentrion, 2013)
Keywords: Fourrure; Guerre; La Corne, Luc de (La Corne Saint-Luc ou Saint-Luc de La Corne); Marchands; Noblesse

Gustave Papineau (1829-1851), le dernier fils de Louis-Joseph - Aubin, Georges (Montréal en tête, 2012)
Keywords: Avenir (L'); Journalistes; Papineau (famille); Papineau, Louis-Joseph

Le réseau de régulation sociale montréalais - Fecteau, Jean-Marie; Harvey, Janice (Histoire de Montréal et de sa région, 2012)
Keywords: Communautés religieuses; Femmes; Hôpitaux; Pauvreté

Population, identités sociales et vie quotidienne - Gauvreau, Danielle (Histoire de Montréal et de sa région, 2012)
Keywords: Famille; Femmes; Irlandais; Mortalité; Travail; Veuvage

Journaux personnels des filles de Pierre-Joseph Oliver Chauveau (1855-1876). Une première approche - Mathieu, Jocelyne (Les Cahiers des Dix, 2012)
Keywords: Bourgeoisie; Chauveau, Pierre-Joseph-Olivier

Le travail et la classe ouvrière montréalaise au XIXe siècle - Petitclerc, Martin (Histoire de Montréal et de sa région, 2012)
Keywords: Chevaliers du Travail; Conseil des métiers et du travail de Montréal; Grande Association; Grèves; Pauvreté; Syndicats internationaux; Travail

Moeurs, sociabilités et mentalités montréalaises: la vie quotidienne dans la ville au XVIIIe siècle - Turcot, Laurent (Histoire de Montréal et de sa région, 2012)
Keywords: Auberges; Cabarets; Danse; Hôtellerie; Marchés; Rues; Théâtre; Vêtements

Immigration et alimentation à Montréal aux XVIIe et XVIIIe siècles: essai d’interprétation à partir d’analyses isotopiques sur des populations archéologiques - Vigeant, Jacinthe (Université de Montréal, 2012)
Keywords: Alimentation

Dans le Montréal de Papineau. L'aventure de Serafino Giraldi - Aubin, Georges (Montréal en tête, 2011)
Keywords: Hôtellerie; Italiens; Papineau (famille); Papineau, Louis-Joseph

Wife to Widow: Lives, Laws, and Politics in Nineteenth-Century Montreal - Bradbury, Bettina (University of British Columbia Press, 2011)
Keywords: Femmes; Veuvage

La société montréalaise au tournant des années 1750. Montréal, citadelle et... ville ouverte - Major, Éric (Montréal en tête, 2011)

Aspects démographiques de la vie des couturières de Montréal au XVIIIe siècle - Gousse, Suzanne (Cahiers d'histoire, 2010)
Keywords: Confection; Femmes

Rosalie Jetté et les filles-mères au XIXe siècle - Lachance, Micheline (Histoire, 2010)
Keywords: Cadron, Marie-Rosalie; Communautés religieuses; Soeurs de Miséricorde

Un singulier cousinage Louis-Joseph Papineau et Jacques Viger - Beaudoin, Léo (Montréal en tête, 2009)
Keywords: Députés; Maires; Papineau, Louis-Joseph; Partis politiques; Viger, Jacques

Un singulier cousinage Louis-Joseph Papineau et Jacques Viger. 3. Les années difficiles - Beaudoin, Léo (Montréal en tête, 2009)
Keywords: Maires; Papineau, Louis-Joseph; Rébellions; Viger, Jacques

William Notman’s Portrait Photographs of the Wealthy English-speaking Girls of Montreal: Representations of Informal Female Education in Relation to John Ruskin’s “Of Queens’ Gardens” and Writings by and for Canadians from the 1850s to 1890s - Lerner, Loren Ruth (Revue d'histoire de l'éducation / Historical Studies in Education, 2009)
Keywords: Bourgeoisie; Femmes

Un singulier cousinage Louis-Joseph Papineau et Jacques Viger - Beaudoin, Léo (Montréal en tête, 2008)
Keywords: Papineau, Louis-Joseph; Viger, Jacques

Rosalie Jetté et les filles-mères: entre tutelle religieuse et pouvoir médical (1845-1866) - Lachance, Micheline (Université du Québec à Montréal, 2007)
Keywords: Cadron, Marie-Rosalie; Communautés religieuses; Soeurs de Miséricorde

Fous, prodigues et ivrognes. Familles et déviances au XIXe siècle - Nootens, Thierry (Study on the History of Quebec/Études d'histoire du Québec, 2007)
Keywords: Délinquance; Famille; Tribunaux

Nous protégeons l'infortune. Les origines populaires de l'économie sociale au Québec - Petitclerc, Martin (VLB, 2007)
Keywords: Assurance; Banques; Pauvreté; Union Saint-Joseph

Rapport sur la question du logement à Montréal; phase 1 - Roy, Christian (Laboratoire d'histoire et de patrimoine de Montréal, 2007)
Keywords: Locataires; Logement; Pauvreté

Fighting from Home. The Second World War in Verdun, Quebec - Durflinger, Serge Marc (Studies in Canadian Military History Series, 2006)
Keywords: Guerre; Quartiers; Verdun

Marie-Marguerite de La Corne Viger 1775-1845. Dame de noblesse canadienne - Beaudoin, Léo (Montréal en tête, 2005)
Keywords: La Corne, Luc de (La Corne Saint-Luc ou Saint-Luc de La Corne); Lacorne (famille); Noblesse; Viger, Jacques

Marie-Marguerite de La Corne Viger 1775-1845. Dame de noblesse canadienne. Madame Jacques Viger - Beaudoin, Léo (Montréal en tête, 2005)
Keywords: Famille; Mariage; Noblesse; Viger, Jacques

Marie-Marguerite de La Corne Viger 1775-1845. Dame de noblesse canadienne (suite)* - Beaudoin, Léo (Montréal en tête, 2005)
Keywords: La Corne, Luc de (La Corne Saint-Luc ou Saint-Luc de La Corne); Lacorne (famille); Noblesse; Viger, Jacques

BARTHE, ÉMILIE (Lavergne) - Bélanger, Réal (Dictionnaire biographique du Canada, 2005)

Introduction: Negotiating Identities in Nineteenth- and Twentieth-Century Montreal - Bradbury, Bettina; Myers, Tamara (Negotiating Identities in 19th- and 20th- Century Montreal, 2005)

Les Madelinots à Verdun - Carbonneau, Pauline (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2005)
Keywords: Quartiers; Verdun

Famille, affaires et succession, les enjeux de la gestion seigneuriale au Canada. Étude de la région montréalaise des 17e et 18e siècles - Couvrette, Sébastien (Histoire Québec, 2005)
Keywords: Famille; Seigneurie

Le cimetière Saint-Antoine. Inventaire archéologique (phase 2), Square Dorchester et Place du Canada, BiFj-37, Montréal 2001 - Ethnoscop (Patrimoine archéologique de Montréal, 2005)
Keywords: Cimetières; Dominion (square); Places publiques; Squares

Une culture matérielle riche dans le « Red Light » de Montréal: Inventaire et fouille archéologiques au faubourg Saint-Laurent MTL03-25-3, MTL03-25-2 et BjFj-121, 2003: Vieux-Montréal et faubourgs - Ethnoscop (Ville de Montréal, 2005)
Keywords: Faubourgs; Logement; Quartiers; Saint-Laurent (quartier)

Le cimetière Saint-Antoine. Étude de potentiel et inventaire archéologiques (Phase 1) du square Dorchester et de la place du Canada, BiFj-37, Montréal - Ethnoscop; Groupe Cardinal Hardy (Patrimoine archéologique de Montréal, 2005)
Keywords: Cimetières; Dominion (square); Places publiques; Squares

Le nectar et l’ambroisie. La consommation des boissons alcooliques chez l’élite de la Nouvelle-France au XVIIIe siècle - Ferland, Catherine (Revue d'histoire de l'Amérique française, 2005)
Keywords: Alcool; Bourgeoisie

BICKERDIKE, ROBERT - Jedwab, Jack (Dictionnaire biographique du Canada, 2005)

« What a Misfortune that Poor Child Should Have Married Such a Being as Joe »: Les fils prodigues de la bourgeoisie montréalaise, 1850-1900 - Nootens, Thierry (Canadian Historical Review, 2005)
Keywords: Bourgeoisie

Bonds of Friendship, Kinship, and Community: Gender, Homelessness, and Mutual Aid in Early-Nineteenth-Century Montreal - Poutanen, Mary Anne (Negotiating Identities in 19th- and 20th- Century Montreal, 2005)
Keywords: Femmes; Itinérance

La famille et le marché de la main-d’œuvre dans les campagnes montréalaises en 1765 - Dépatie, Sylvie (Familles, terre, marchés: logiques économiques et stratégies dans les milieux ruraux (XVII-XXe siècles), 2004)
Keywords: Famille

Une forme d'entraide populaire: histoire des sociétés québécoises de secours mutuels au 19e siècle - Petitclerc, Martin (Université du Québec à Montréal, 2004)
Keywords: Assurance; Banques; Pauvreté; Union Saint-Joseph

Spécial patrimoine bâti (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2003)
Keywords: Bourgeoisie; Logement; Patrimoine; Quartiers; Rues; Verdun

La vie de château - Dugas, Marcel (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2003)
Keywords: Bourgeoisie; Château Dufresne; Golden Square Mile; Logement; Mount Stephen Club

Fous, prodigues et ivrognes: internormativité et déviance à Montréal au 19e siècle - Nootens, Thierry (Université du Québec à Montréal, 2003)
Keywords: Alcool; Famille; Hôpitaux; Hôpitaux psychiatriques; Médecine

Images du danger dans les archives judiciaires. Comprendre la violence et le vagabondage dans un centre urbain du début du XIXe siècle, Montréal (1820-1842) - Poutanen, Mary Anne (Revue d'histoire de l'Amérique française, 2002)
Keywords: Délinquance; Itinérance

Black Media in Montreal: In Defense of Abyssinia - Williams, Dorothy (Proceedings of the Seventh Annual History in the Making Conference: History and Media, Concordia University, March 2001, 2002)
Keywords: Esclaves; Journalistes; Noirs

Le suicide dans le district judiciaire de Montréal (de 1815 à 1843 et de 1893 à 1903) - Bordeleau, François (Université du Québec à Montréal, 2001)
Keywords: Mortalité

La vie quotidienne dans la vallée du Saint-Laurent, 1790-1835 - Hardy, Jean-Pierre (Septentrion et Musée canadien des civilisations, 2001)

The Protestant Orphan Asylum and the Montreal Ladies' Benevolent Society: A Case Study in Protestant Child Charity in Montreal, 1822-1900 - Harvey, Janice (Université McGill, 2001)
Keywords: Enfants; Famille; Femmes; Montreal Ladies' Benevolent Society; Protestants

Vagabons [sic] et sans abris à Montréal: perception et prise en charge de l'errance, 1840-1925 - Aranguiz, Marcela (Regroupement des chercheurs-chercheures en histoire des travailleurs et travailleuses du Québec, 2000)
Keywords: Itinérance; Pauvreté

A New World from Two Old Ones: the Evolution of Montreal's tenements, 1850-1892 - Dufaux, François (Urban Morphology, 2000)
Keywords: Logement

Faubourg Québec: la ville conviviale - Dufaux, François (Continuité, 2000)
Keywords: Centre-sud (quartier); Faubourgs; Logement; Quartiers

Feathering Her Nest in Nineteenth-Century Montreal - Olson, Sherry (Histoire sociale / Social History, 2000)
Keywords: Rues

The Homeless, the Whore, the Drunkard, and the Disorderly: Contours of Female Vagrancy in the Montreal Courts, 1810-1842 - Poutanen, Mary Anne (Gendered Pasts: Historical Essays in Femininity and Masculinity in Canada, 1999)
Keywords: Délinquance; Femmes; Itinérance; Prostitution

Place d'Youville à Montréal: évolution des modes de vie aux abords de la rivière Saint-Pierre entre 1775 et 1838 - Roy, Christian (Archéologiques, 1999)
Keywords: Artisans; Youville (place d')

Claims on Housing Space in Nineteenth-Century Montreal - Gilliland, Jason A.; Olson, Sherry (Urban History Review / Revue d'histoire urbaine, 1998)
Keywords: Famille; Logement; Mobilité résidentielle

Debating Dower: Patriarchy, Capitalism and Widows' Rights in Lower Canada» - Bradbury, Bettina (Power, Place and Identity: Historical Studies of Social and Legal Regulation in Quebec, 1998)
Keywords: Femmes; Mariage; Veuvage

Shadrach Minkins: From Fugitive Slave to Citizen - Collison, Gary (Harvard University Press, 1998)
Keywords: Esclaves; Noirs

Modeling Residential Mobility in Montreal, 1860-1900 - Gilliland, Jason A. (Historical Methods, 1998)
Keywords: Famille; Logement; Mobilité résidentielle

BURLAND, JEFFREY HALE - Keating, Peter (Dictionnaire biographique du Canada, 1998)

"Pour se créer un avenir". Stratégies de couples montréalais au XIXe siècle - Olson, Sherry (Revue d'histoire de l'Amérique française, 1998)
Keywords: Famille

The Geography of Prostitution in an Early Nineteenth-Century Urban Centre: Montreal, 1810-1842 - Poutanen, Mary Anne (Power, Place and Identity: Historical Studies of Social and Legal Regulation in Quebec, 1998)
Keywords: Femmes; Prostitution

Class, Culture, Family and the Law: Wife to Widow in Nineteenth-Century Quebec - Bradbury, Bettina (Programme d'études sur le Québec de l'Université McGill, 1997)
Keywords: Femmes; Mariage; Veuvage

La naissance du confort, ou, La mutation de la vie quotidienne dans la vallée du Saint-Laurent (1790-1835) - Hardy, Jean-Pierre (Université de Montréal, 1997)

Familles de charpentiers et de menuisiers à Montréal au XVIIIe siècle: alliances matrimoniales et reproduction sociale - Langlois, France-Isabelle (Université de Montréal, 1997)
Keywords: Charpentiers; Famille; Mariage; Menuisiers

To Indulge their Carnal Appetites: Prostitution in Early Nineteenth-Century Montreal, 1810-1842 - Poutanen, Mary Anne (Université de Montréal, 1997)
Keywords: Police; Prostitution; Tribunaux

Romanticism, Home, and Death: Elements in the Lives of the Anglophone Elite in Early Victorian Montreal - Young, Brian (Australian-Canadian Studies, 1997)
Keywords: Anglophones

Les "enfants du roi" dans le gouvernement de Montréal - Bouchard, Yoland (Les marginaux, les exclus et l'autre au Canada aux XVIIe et XVIIIe siècles, 1996)
Keywords: Enfants; Hôpital Général; Hôpitaux

Les vieillards dans le gouvernement de Montréal - Léveillé, Daniel; Lachance, André (Les marginaux, les exclus et l'autre au Canada aux XVIIe et XVIIIe siècles, 1996)
Keywords: Hôpital Général; Hôpitaux

Familles ouvrières à Montréal. Âge, genre et survie quotidienne pendant la phase d’industrialisation - Bradbury, Bettina (Boréal, 1995)
Keywords: Alimentation; Famille; Logement; Vêtements

Les procès en séparation de corps dans la région de Montréal, 1795-1879 - Cliche, Marie-Aimée (Revue d'histoire de l'Amérique française, 1995)
Keywords: Femmes; Mariage

La consommation de viande à Montréal au XVIIe et au XVIIIe siècles - Cossette, Évelyne (Archéologies québécoises, 1995)
Keywords: Alimentation; Auberges; Champ-de-Mars; Fortifications; Hôpital Général; Hôpitaux; Place Royale; Places publiques; Wurtele, Jacob

Le choléra de 1832 dans le Bas-Canada: mesure des inégalités devant la mort - Dechêne, Louise; Robert, Jean-Claude (Santé et société au Québec: XIXe-XXe siècle, 1995)
Keywords: Choléra; Mortalité; Épidémies

Le problème de l'alcoolisme au Canada français: discours élitaires et mouvements sociaux - Glaude, Rolland (Université de Sherbrooke, 1995)
Keywords: Alcool; Médecine

Le raz de marée irlandais à Montréal - Olson, Sherry; Thornton, Patricia (Les chemins de la migration en Belgique et au Québec: XVIIe-XXe siècles, 1995)
Keywords: Irlandais

La culture matérielle des Canadiens au XVIIIe siècle: analyse du niveau de vie des artisans du fer - Bouchard, Dominique (Revue d'histoire de l'Amérique française, 1994)
Keywords: Artisans; Fer et acier

Women and Technological Change in Nineteenth Century Montreal - Bradbury, Bettina (Women, Work and Place, 1994)
Keywords: Femmes

Working Families: Age, Gender and Daily Survival in Industrializing Montreal - Bradbury, Bettina (Labour / Le travail, 1994)
Keywords: Famille; Femmes

The Fragmented Family: Family Strategies in the Face of Death, Illness and Poverty, Montreal, 1860-1885 - Bradbury, Bettina (Family Patterns, Gender Relations, 1993)
Keywords: Famille; Orphelinats

Working Families: Age, Gender, and Daily Survival in Industrializing Montreal - Bradbury, Bettina (McClelland & Stewart, 1993)
Keywords: Famille; Femmes

Property and Marriage: the Law and the Practice in Early Nineteenth-Century Montreal - Bradbury, Bettina; Stewart, Alan; Kolish, Evelyn; Gossage, Peter (Histoire sociale / Social History, 1993)
Keywords: Droit; Mariage

Eating in the City: Food Provisioning in Montreal in the Early Nineteenth Century - Fyson, Donald (Actes du colloque « La distribution alimentaire », 1993)
Keywords: Alimentation

Class, Gender and the Law in Eighteenth and Nineteenth Century Quebec: Sources and Perspectives - Fyson, Donald; M. Coates, Colin; Harvey, Kathryn (Occasional Papers of the Montreal History Group, 1993)
Keywords: Criminalité; Mariage; Police; Prostitution; Travail; Tribunaux

Residential Mobility in Montreal, 1861-1901 - Gilliland, Jason A. (Université McGill, 1993)
Keywords: Famille; Logement; Mobilité résidentielle

Marriage Contracts as a Source for Historians - M. Stewart, Alan; Bradbury, Bettina (Class, Gender and the Law in Eighteenth and Nineteenth Century Quebec: Sources and Perspectives, 1993)
Keywords: Mariage

Reflections of Montreal Prostitution in the Records of the Lower Courts, 1810-1842 - Poutanen, Mary-Anne (Class, Gender and the Law in Eighteenth and Nineteenth Century Quebec: Sources and Perspectives, 1993)
Keywords: Criminalité; Police; Prostitution; Tribunaux

Le niveau de vie des artisans du fer à Montréal et à Québec entre 1730 et 1780 - Bouchard, Dominique (Université de Montréal, 1992)
Keywords: Artisans; Fer et acier

Pigs, Cows and Boarders. Non-wage forms of Survival among Montreal Families, 1861-1881 - Bradbury, Bettina (The Challenge of Modernity: A Reader in Post-Confederation Canada, 1992)
Keywords: Famille; Femmes

L’organisation communautaire et les mutations dans les services sociaux au Québec, 1961 – 1991. La marge et le mouvement comme lieux de l’identité - Doré, Gérald (Service social, 1992)
Keywords: Centres locaux de services communautaires (CLSC); Groupes populaires

Le festin de Lady Cartier: La table et l’étiquette au Québec, vers 1865 - Fortier, Yvan (Continuité, 1992)
Keywords: Cartier, George-Étienne; Domestiques

Du pain au madère: L’alimentation à Montréal au début du XIXe siècle - Fyson, Donald (Revue d'histoire de l'Amérique française, 1992)
Keywords: Alimentation

Montréal, métropole du Québec. Images oubliées de la vie quotidienne 1852-1910 - Lessard, Michel (Éditions de l'Homme, 1992)
Keywords: Métropole; Photographie

Familles montréalaises du XIXe siècle: trois cultures, trois trajectoires - Olson, Sherry; Thornton, Patricia (Cahiers québécois de démographie, 1992)
Keywords: Anglophones; Famille; Irlandais

Le niveau de vie et l'univers domestique des artisans montréalais entre 1740 et 1809 - Desbiens, Josée (Université de Montréal, 1991)
Keywords: Artisans

Aspects sociaux et économiques du veuvage à Montréal au milieu du 19e siècle - Favel, Valentine (Université Lumière Lyon 2, 1991)
Keywords: Famille; Femmes; Veuvage

Smoke and Fire: The Chinese in Montreal - Kwok Bun, Chan (The Chinese University Press, 1991)
Keywords: Chinois

La Place Royale par le menu, mémoires pour l'an 2000, Montréal, son histoire et son patrimoine - Bizier, Hélène-Andrée (Ville de Montréal, Service des affaires corporatives, Module des communications, 1989)
Keywords: Alimentation; Hôtellerie; Place Royale; Places publiques; Wurtele, Jacob

Surviving as a Widow in 19th - Century Montreal - Bradbury, Bettina (Urban History Review / Revue d'histoire urbaine, 1989)
Keywords: Famille; Femmes; Veuvage

Eating in the City: Diet and Provisioning in Early Nineteenth Century Montreal - Fyson, Donald William (Université McGill, 1989)
Keywords: Alimentation

The Fragmented Family: Family Strategies in the Face of Death, Illness, and Poverty, Montreal, 1860-1885 - Bradbury, Bettina (Family Bonds and Gender Divisions: Readings in the Sociology of the Family, 1988)
Keywords: Famille; Orphelinats

Les inventaires de biens après décès et la civilisation matérielle dans les plaines de Caen et de Montréal, 1740-1780 - Cardin, Martine; Dickinson, John A. (Sociétés villageoises et rapports villes-campagnes au Québec et dans la France de l'ouest XVIIe-XXe siècles, 1987)
Keywords: Mortalité; Notaires

Extrait de la vie domestique d'une famille de cultivateur et d'artisan du faubourg Saint-Louis, 1745-1825, site Viger, Montréal - Laliberté, Monique (Société d'archéologie et de numismatique de Montréal, 1986)
Keywords: Artisans; Famille; Faubourgs; Quartiers; Saint-Louis

Habiter un nouveau quartier ouvrier de la banlieue de Montréal; village Saint-Augustin (Municipalité de Saint-Henri) 1855-1881 - Lauzon, Gilles (Université du Québec à Montréal, 1986)
Keywords: Logement; Quartiers; Saint-Augustin; Saint-Henri

Pigs, Cows, and Boarders: Non-Wage Forms of Survival among Montreal Families, 1861-91 - Bradbury, Bettina (Labour / Le travail, 1984)
Keywords: Famille; Femmes

The Working-Class Family Economy: Montreal, 1861-1881 - Bradbury, Bettina (Université Concordia, 1984)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

Absorbing Junior: the Use of Patent Medicines as abortifacients in Nineteenth Century Montreal - Gossage, Peter (The Register, 1982)
Keywords: Avortement; Femmes; Médecine

The Fragmented Family: Family Strategies in the Face of Death, Illness, and Poverty, Montreal, 1860-1885 - Bradbury, Bettina (Childhood and Family in Canadian History, 1982)
Keywords: Famille; Orphelinats

Un repas d'apparat chez George-Étienne Cartier. La table et l'étiquette à Montréal vers 1865 - Fortier, Yvan (Parcs Canada, 1981)
Keywords: Cartier, George-Étienne; Domestiques

The Winter's Tale: The Seasonal Contours of Pre-Industrial Poverty, in British North America 1815-1860 - Fingard, Judith (CHA / SHC, Historical Papers / Communications historiques, 1974)
Keywords: Pauvreté

La condition des travailleurs, 1851-1896 - Bernier, Jacques (Les travailleurs québécois, 1851-1896, 1973)

Scènes de rues à Montréal au siècle passé - Massicotte, E.-Z. (Les Cahiers des Dix, 1942)
Keywords: Rues

The Case of the Canadians of Montreal Distressed by Fire (s.-é., 1865)
Keywords: Incendies